Preparation of quantum dot luminescent materials through the ink approach. (5th February 2016) - Wei, Wenjun; Xu, Heng; You, Qingliang; Cheng, Qi; Liu, Cui; Zou, Linling; Liu, Xueqing; Liu, Jiyan; Cao, Yuan-Cheng; Zheng, Guang
Abstract: Highly transparent and luminescent UV curable polyurethane acrylate/quantum dot (QD) nanocomposite material was prepared using "QD inks" approach by UV curing. First, water soluble CdTe QDs (λem  = 510 nm, 540 nm and 620 nm) were synthesized. Urethane acrylate prepolymer was used as the media for the "QD ink" and 2-hydroxy-2-methylpropiophenone (HMPF, also called 1173) was used as the photoinitiator. FT-IR spectra showed that there were strong vibrations at 1725 cm − 1 which was contributed from the –CO groups after the polymerization, while the end –CCH2 group vibration at 964 cm − 1 and 993 cm − 1 disappeared. Thermogravimetric analysis of the resultants showed the 5% weight loss up to 150 °C which was the free water content; and 9.18% loss of the weight was the dehydrate of the resins in 150 °C–301.75 °C; weight loss of 93% from 300 °C to 450 °C was the decomposition. Mechanical tests showed that the elongation at break was 12.96%, and that the tensile strength was 5.39 MPa. This "QD ink" approach is attractive in the preparation of luminescent materials and thus is prospective in the development of QD devices. Graphical abstract: Highlights: Quantum dot luminescent films were prepared by "ink" approach using urethane acrylate. This "quantum dot ink" has better polymer–particle interfacial adhesion and can overcome quantum dot aggregation. This approach is promising to prepare quantum dot related luminescent device components.